The Importance of 'Risk Radar' in Software Risk Management: A Case of a Malaysian Company - Suda, K.; Abdul Rani, Nazatul Shima (Centre for Promoting Ideas, 2010)
‘Risk radar’ is applied to a company in Malaysia, a discussion on the implementation, implications and recommendation highlighted in this paper. The scope of this study has been an analysis of risk management and risk exposure of software projects practices in the company. This study also provided the evident that the successes of the several software that goes into the Malaysian market, depending on how risk management and its plan in software development as in the case of the selected company. It also exposed on how significant is the risk management contributing to cost effective and growth. Findings also included using 80/20 rules or Pareto Principle, 80% of the risks item listed by Boehm in Ten (10) Top Risks are due to 20% of sources (i.e. soft risks). Empirical studies have shown that 80% of the software rework comes from 20% of the problems, and that many of these critical problems involve neglect of off nominal requirements and all these negligence are caused by human (soft risk) (Boehm, 1989; Boehm-Basili, 2001; Standish Group Chaos Study Report (STANDISH), 1995).The company must implement the propose system to ensure that good practice and successful implementation of software risk management is the key factor to successful creation of software that are marketable and high quality benchmarking of plant industrial solutions. It could contribute to gain competitive advantage by at least 50% of project cost due to risks such as rework, budget overruns cost overrun, content deficiencies and etc.; ability to sustain due to minimum impact by software risks; and ability to own the technology rather than uses the technology with reasonable cost in development and always meet or exceed customer requirements.